-Differential operators and -differential modules for the Virasoro algebra. Issue 7 (3rd July 2019) - Liu, Xuewen; Guo, Li; Guo, Xiangqian
ABSTRACT: The concept of λ -differential operators is a natural generalization of differential operators and difference operators. In this paper, we determine the λ -differential Lie algebraic structure on the Witt algebra and the Virasoro algebra for invertible λ . Then we consider several families of modules over the Virasoro algebra with explicit module actions and determine the λ -differential module structures on them.